Illegal wildlife trade in two special economic zones in Laos: Underground–open-sale fluctuations in the Golden Triangle borderlands - van Uhm, Daan P.; Zhang, Mingxia (Frontiers in Conservation Science, 2022)
The Laos borders with China, Myanmar and Thailand have been identified as vulnerable hubs for illegal wildlife trade. In particular, some special economic zones (SEZs) in Laos are linked to illegal wildlife products, including tiger bones, rhino horn and ivory for sale. SEZs are zones granted more free market-oriented economic policies and flexible governmental measures. In this study, we conducted on-site observations to identify high-valued wildlife, including (parts of) tigers, rhinos, bears, and pangolins in 2 of the 13 SEZs - the Golden Triangle and Boten SEZ - and conducted semi-structured interviews with anonymous participants in 2017 and 2019. The trend regarding illegal wildlife trade in these SEZs seems to fluctuate. We found that in the Golden Triangle SEZ the illegal trade in wildlife is present, but occurs more covertly than previously observed; the trade transformed underground, to online social media. In Boten SEZ, we found a decrease in bear bile products and an increase in the volume of tiger products openly for sale. Informants explained that the decrease of openly sold wildlife in the Golden Triangle SEZ has been influenced by media and political attention as well as inspections from local authorities, while in Boten SEZ illegal wildlife traders diversified into tiger products, due to the decline in bear bile products and the reduction in opportunity to obtain them.